Dynamics of regime failure: Regime power analysis China-ASEAN illicit drug control - Yongjin, Huang (Jurnal Inovasi Ilmu Sosial dan Politik (JISoP), 2025)
The East and Southeast Asian region confronts complex challenges in combating the illicit drug trade originating from the Golden Triangle, a long-established narcotics trade hub. In 2000, China and ASEAN countries cooperated through the ACCORD as a comprehensive framework of regional drug control. However, the increasing number of methamphetamine seizures and the rise of new psychoactive substances indicate persistent challenges in the power of ACCORD's drug control regime. Hence, this study aims to analyze the ASEAN- China cooperation framework, particularly in the context of regime power formation. The concept of the International Security Regime is utilized to understand the complexity of the regime by integrating four dimensions of power, namely productive, structural, institutional, and compulsory. Through a qualitative approach and secondary analysis, this study reveals complex dynamics that affect the effectiveness of regional cooperation from the existing literature.  First, productive power faces significant challenges due to intra-regional diversity, complex bilateral relations, and the declarative nature of ACCORD. Second, structural power is compromised due to power asymmetries and deep contestation. Third, institutional power suffers from significant weaknesses due to flawed institutional design. Fourth, compulsory power suffers because China's ability to exercise compulsion power directly, such as through sanctions or pressure, is limited within the multilateral framework of ACCORD. Therefore, cooperation needs to strengthen the network of normative discourse, political structures, and institutions, which affects the power drugs control regime. This paper successfully highlights the weaknesses in the power of the ASEAN-China-constructed international security regime.